2021
DOI: 10.26656/fr.2017.5(6).328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different thin layer drying temperatures on the drying time and quality of butterfly pea flowers

Abstract: With attractive flower colours ranging from dark green to purple, Butterfly pea (Clitoria ternatea L.) is grown year-round in Vietnam. The purpose of this study is to determine the effect of air temperature on drying time and antioxidant compounds of Butterfly pea flowers, fitting the drying curves and testing the goodness of fit. In this study, air drying characteristics of the Butterfly pea flowers were determined using drying air temperature from 55oC to 70oC at a constant air velocity of 1 m/s. The data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Further more, higher thermal energy promotes the movement of water molecules in the food resulting in a reduction in drying time with increasing drying temperature [38]. Thes results are quite similar to previous studies reported on different plant food such a blanched pumpkin slices [39], butterfly pea flowers [10], and mango slices [40].…”
Section: Drying Kineticssupporting
confidence: 87%
See 4 more Smart Citations
“…Further more, higher thermal energy promotes the movement of water molecules in the food resulting in a reduction in drying time with increasing drying temperature [38]. Thes results are quite similar to previous studies reported on different plant food such a blanched pumpkin slices [39], butterfly pea flowers [10], and mango slices [40].…”
Section: Drying Kineticssupporting
confidence: 87%
“…Drying of the stable foam structure will make an important contribution to the improvement of moisture transmission, as the surface area increases due to air incorporation with foaming [4]. The low temperature and short drying time of foam mat drying were chosen to maintain the available nutrients present in the extract [10,31].…”
Section: Dryingmentioning
confidence: 99%
See 3 more Smart Citations